Assessing and Improving Access to Health and Social Care Services for Children Rendered Vulnerable by Abuse: Protocol for a Cross-Sectoral Longitudinal, Mixed Methods, Multi-Country Study Using Nationwide Data in Europe - Quantin, Catherine; O'Leary, Donna; Shenderovich, Yulia; Batura, Neha; Broccia, Marcella; Cottenet, Jonathan; Cowley, Laura; Graesholt-Knudsen, Troels; Lamela, Diogo; Lalor, Kevin; Jud, Andreas; Hakkaart-van Roijen, Leona; et al. (International Journal of Population Data Science, 2026)
Child maltreatment (CM) is a widespread and underreported public health concern with long-term health and wellbeing outcomes. In Europe, access to timely, effective support remains limited. Inadequate responses exacerbate long-term outcomes and influence life course trajectories, with substantial societal and economic costs. The EU-funded SERENA project aims to improve access to health and social care (HSC) services for individuals who experience CM throughout Europe by enhancing detection and interventions, limiting consequences, and reducing societal burdens. SERENA takes an early life course approach, and will examine HSC pathways before and after CM detection, assess related health and wellbeing outcomes, and evaluate the societal costs of CM. Two scoping reviews will examine quantitative and qualitative evidence on barriers and facilitators to access to HSC for children who experience CM, and their service pathways. A mixed methods study will combine quantitative analyses of nationwide longitudinal administrative HSC data from seven countries, supplemented by aggregated child protection data from 26 countries, with qualitative analyses of interviews with adult survivors of CM and HSC professionals in three countries. Examination of HSC pathways will enable us to identify the settings and stages where interventions can be targeted to improve outcomes for children with CM. We will also examine societal costs by analysing direct medical expenses, educational costs, and productivity losses in four countries. An interdisciplinary, participatory synthesis involving stakeholders and adult survivors of CM will assess services, define priority actions, and inform recommendations. SERENA, a consortium of 22 partners across Europe, represents the first multi-country, large-scale, cross-sectoral longitudinal initiative to comprehensively examine CM and HSC service use. By addressing critical evidence gaps, SERENA will provide operationally and economically viable recommendations to enhance service access and public health responses in Europe, with findings that are transferable to diverse international contexts.